Lensa Netnografi: Analisis Sentimen Untuk Peningkatan Engagement Konten Promosi Pariwisata Melalui Film “The Last Of Us 2 - Swandeni, Ni Kadek; Indrayani, I Gusti Ayu Putu Wita; Trisdayanti, Ni Putu Eka; Darmaputra, Putu Gede Eka; Tirtawati, Ni Made (Jurnal Ilmiah Pariwisata, 2024)
This study aims to analyze sentiments in the Instagram post @kemenparekraf.ri regarding the film "The Last of Us 2" and its impact on increasing engagement in promotional content through an infrequently employed approach. The research intends to investigate the effect of using dramatic content in promoting the film "The Last of Us 2" on the Instagram account @kemenparekraf.ri in enhancing audience engagement using a netnography approach. A qualitative research method was employed by collecting data through online observation of content posted on January 24, 2023. Findings indicate that the use of dramatic content significantly increased audience engagement, with an engagement rate reaching 17.7%, although the majority of sentiments expressed were negative. The practical implications of this research are to provide recommendations for government social media managers to exercise greater caution in determining promotional content, while theoretically contributing to the understanding of the netnography approach in the context of tourism promotion. Keywords: netnography, promotion, sentiment, tourism